What a dog knows [large type] - Wilson, Susan, 1951- (Thorndike Press large print basic, 2022)
"Ruby Heartwood has spent her life running away. Away from the orphanage where she was left as a newborn, away from those who exploited her, and away from the man who raped her. She ran from child welfare authorities as a runaway and teenage mother. She's never stayed put. She's never felt connected. Until now. Ruby is a psychic, a fortune teller. She has spent most of her life working at street fairs, carnivals, and the odd Renaissance Faire. Of late, her abilities to tell a person's fortune have been declining. One night she pulls off the road during a violent thunderstorm, sheltering in her Volkswagen Westfalia. At the storm's height, a bolt of lightning leaves Ruby shaken--and changes her life. As the storm clears, Ruby finds a visitor sitting outside her van door: a little dog who says, quite distinctly, Let me in. Ruby has woken up able to hear the thoughts of animals, so she adds that to her list of psychic offerings and signs up for the Harmony Farms Farmers' Market and Makers Faire. With the little Hitchhiker, her fast friend and her familiar, Ruby finds herself lingering in Harmony Farms. At the same time, she is haunted by dreams that lead her to wonder if she hasn't been running away all this time, but running toward something--or someone"--